Strategy for longan drying in two-stage superheated steam and hot air - Thanutyot Somjai (2018)
The aim of this research was to investigate a novel strategy and to develop a model for longan without stone drying using a two-stage SSD + HAD process (superheated-steam drying followed by hot air drying). The experiments were conducted using superheated-steam at: 120, 140, 160, and 180 °C followed by hot air at: 60 and 70 °C. The moisture content of longan at the end of the first-stage drying was about 200% dry basis. The effects of superheated steam and air temperatures on the drying kinetics and quality of dried longan viz. color, shrinkage, and microstructure were determined. A mathematical model has been developed to predict the moisture content of longan, the drying temperature at the outlet of the drying chamber and the drying rate. Comparisons showed that the simulated results were in agreement with experimental values. SSD + HAD using 180 °C superheated steam, followed by 70 °C hot air was the most suitable drying condition for drying longan. © 2009 Elsevier Ltd. All rights reserved.